The Impact and Challenges of Education and Administration in VET on Economic Growth in Oman During the COVID-19 Period - Alzadjali, Amna; Altinay, Fahriye; Dagli, Gokmen (Frontiers in Psychology, 2022)
The COVID-19 pandemic was a major global health problem that had substantial consequences for people's daily lives. This research aims to evaluate the impact of education and administration in vocational education and training (VET) on economic growth in Oman and to discuss the possible challenges during the COVID-19 period. The quantitative data were gathered using an online interview questionnaire from 108 randomly selected students and college staff to collect qualitative data. The study revealed that administration plays an important role in economic growth. Many students suggested that the national administration, which is the government, should invest much capital in the education system from primary level to tertiary level. If the government does not provide finances to boost the education sector, education would face extra difficulties after the covid 19 peroid. Furthermore, students raised that the administration should provide a national vision in various sectors of its ministries to meet its goals.